Programma: 31 maart: Pop Staples, Larry McCray, Steve Roux; 9 april: Etienne Daho; 11 april: Taraf de Haïdouks; 12 april: Ein stuzende Neu Bauten (1993)
Programma: 31 maart: Pop Staples, Larry McCray, Steve Roux; 9 april: Etienne Daho; 11 april: Taraf de Haïdouks; 12 april: Ein stuzende Neu Bauten.